2016
DOI: 10.1111/1471-0528.14423
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus associated microcephaly/micrencephaly—fetal brain imaging in comparison with neuropathology

Abstract: virus associated microcephaly/micrencephaly-fetal brain imaging in comparison with neuropathology. BJOG 2017;124:521-525. In December 2015, during the Zika virus (ZIKV) epidemic in Brazil, a possible association between ZIKV infection during pregnancy and fetal brain malformations was suspected due to a 20-fold rise in cases of microcephaly among newborns. 1,2 Several reports published thereafter have strengthened the association between ZIKV and fetal brain damage. [3][4][5][6] Prenatal diagnosis of microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Parenchymal or cerebellar calcification were described in 37 studies of our review [19,23,40,45,59,[62][63][64][65][66][67][68][69][70][71][73][74][75][76][78][79][80][81][82][83][84][85]87,90,91,93,94,[96][97][98]100,101] and also in other review which reported a prevalence of 42.6% [47]. These findings may also be found in congenital infections known by the mnemonic TORCH (Toxoplasmosis, Rubella, Cytomegalovirus (CMV) and Herpes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Parenchymal or cerebellar calcification were described in 37 studies of our review [19,23,40,45,59,[62][63][64][65][66][67][68][69][70][71][73][74][75][76][78][79][80][81][82][83][84][85]87,90,91,93,94,[96][97][98]100,101] and also in other review which reported a prevalence of 42.6% [47]. These findings may also be found in congenital infections known by the mnemonic TORCH (Toxoplasmosis, Rubella, Cytomegalovirus (CMV) and Herpes.…”
Section: Discussionsupporting
confidence: 57%
“…Microcephaly was the most frequent sign found in neonates exposed to ZIKV during pregnancy among the articles in our review [28,[38][39][40][41]. Forty one studies reported microcephaly [19,23,40,45,[58][59][60][62][63][64][65][66][67]69,70,70,71,[73][74][75][76][79][80][81][82][83][84][85][86][87][89][90][91][92][93][94][96][97][98][99][100][101]. Other studies, using different methodologies, have reported similar results [104][105]…”
Section: Discussionmentioning
confidence: 99%
“…In recent ZIKV outbreaks, there was a higher risk/incidence of Guillain-Barre syndrome (GBS) in adults (do Rosário et al, 2016; Paploski et al, 2016) and severe birth defects including fetal microcephaly (now collectively termed as Congenital Zika Syndrome (CZS)), which are directly attributed to ZIKV infection of pregnant women (Calvet et al, 2016; Mlakar et al, 2016; Oliveira et al, 2016; Schuler-Faccini et al, 2016; Vesnaver et al, 2017). Aedes aegypti and Aedes albopictus are the major mosquito vectors for viral transmission (Aliota et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal ZIKV infection during pregnancy is usually asymptomatic for the mothers and can induce severe damage to the fetus similar to that found in the TORCH infections, such as fetal microcephaly, which was reported during the Brazilian epidemic in 2015 (111). Additional damage may include eye injuries, fetal growth restriction, and congenital contractures (112).…”
Section: Fetal and Neonatal Immunitymentioning
confidence: 65%